COVID-19 encephalopathy with severe neurological symptoms: a clinical case presentation with literature review - Baranauskienė, G.; Tutlienė, N.; Kaubrys, G. (Neurologijos seminarai, 2023)
COVID-19 infection is affecting more and more people around the world, and as the number of recovered patients increases, so does the knowledge on the potential clinical signs of the disease. Although SARS-CoV-2 virus is commonly associated with damage to the respiratory system, it has been observed that about half of patients with COVID-19 infection may also develop various neurological symptoms such as anosmia, dysgeusia, headache, myalgia, or dizziness. Encephalopathy is singled out as one of the most severe complications of the central nervous system caused by SARS-CoV-2 virus and associated with longer duration of the disease, increased disability, and mortality. Acute encephalopathy is a disorder of the brain that clinically occurs with a sudden change in the level of consciousness in otherwise healthy patients before the onset of symptoms. Risk factors include older age, male gender, quicker hospitalization after the onset of symptoms, and chronic illnesses. In exceptional cases, encephalopathy may be an early or even a major symptom of COVID-19 in young patients. The pathogenesis of COVID-19 encephalopathy is not fully understood. However, the most likely etiology of encephalopathy is multifactorial: systemic disease response, inflammation, coagulopathy, direct viral neuroinvasion, endoartheritis, and possibly post-infectious autoimmune mechanisms. For patients with suspected changes in the level of consciousness due to coronavirus infection, it is recommended to perform a thorough examination of the cerebrospinal fluid (CSF), head imaging with a preference for magnetic resonance imaging (MRI), and electroencephalography (EEG) It is worth noting that blood or imaging tests often do not show specific changes in patients with encephalopathy. As revealed by some studies of CSF examinations, cytosis is usually absent or very low while the protein concentration remains normal. It is important to note that SARS-CoV-2 is detected in the cerebral fluid only in isolated cases. Although the EEG of patients with COVID-19 are often normal, they sometimes show specific encephalopathic changes including excessive generalized frontal delta waves, triphasic waves and lower amplitude alpha and beta waves. The MRI describes a spectrum of neurovisual abnormalities, the most common of which are foci of leukoencephalopathy, changes in diffusion restriction imaging in the white, rarely in the gray matter, signs of microhaemorrhage and leptomeningitis. Treatment for COVID-19 encephalopathy includes supportive care and symptomatic treatment. Some studies have shown that immune modulation therapy, including high-dose corticosteroids and intravenous immunoglobulins, is effective in some severely ill patients.
Keywords: COVID-19 infection; pandemic; encephalopathy; symptoms